Wind aspects in built environment - Klemm, Katarzyna (Budownictwo i Architektura / Civil and Architectural Engineering, 2022)
The dynamic development of built-up areas observed in the last few decades resulted in strong environmental transformations, especially in terms of climate phenomena. One of the factors which significantly affects the climate and bioclimate of urban areas is wind. Wind can cause discomfort to pedestrians or heat loss in buildings, if the wind speed around buildings is too high. The paper presents two examples of research conducted by the author, related to the issues of wind flow in built-up areas, based on the numerical simulations. The numerical simulations become an increasingly frequently used tool to determine the wind climate. Simulation results provide designers with important information on the influence of the buildings and their layout on the local changes in airflow. They allow testing of alternative solutions and effectiveness of various remedial measures.